MOTIF ORANG TUA MENYEKOLAHKAN ANAKNYA DI SSB GEN-B - Pratama, Valdo Indra (Paradigma, 2021)
The football school is a means of fostering youth football. In this research, the object of this research is SSB Gen-B in Mojokerto City. SSB Gen-B has its own charm for parents who want to send their children to SSB, because the people of Mojokerto and its surroundings have succeeded in producing talented football players who are now members of Indonesian professional clubs. Although SSB Gen-B is expensive, it is not a problem for parents to support their child's talent and interest in football. The purpose of this study was to identify the background and goals to be achieved by the research subjects in sending their children to SSB Gen-B. The method in this study is a qualitative research using Alfred Schutz's phenomenological approach. Alfred Schutz's phenomenology is used to study the because motive and in order to motive of the informants who are parents of SSB Gen-B students. The results of the study are because the informant sends his children to SSB Gen-B because the child is influenced by the association in the surrounding environment, the habits of parents related to football, the child is motivated by his friends, the coercion of parents, and the quality of SSB Gen-B which already proven. Of course, every action of a person has a predetermined purpose. Their in order to motive in sending their children to SSB Gen-B wants the child to become a professional soccer player, teach discipline, introduce the child to a new environment, and maintain the child's physical fitness. Keywords : Gen-B Soccer School, Parents, Social Motive